TEORI MUTAKHIR PEMBELAJARAN: KONSEP EDUTAINMENT DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Ulil Albab (Islamic University of Indonesia, 2018)
Education, in its essence, is the process to direct human into significant development in discovering, nurturing and producing the highest degree of human potential. These diverse human faculties are far wider than education old paradigm intends to achieve: knowledge transformation. Thus, entertaining education tries to actualize conventional learning objectives while maintaining neglected objectives. One of the concept in entertaining education, edutainment, tries to combine two disctinct activities: education and entertainment. In the context of Islamic Education which aims a multidimensional purpose of belief, action, character and being beneficial for both religion and nation, implementing edutainment is a proper act, for it will provide freedom for student to explore knowledges from different sources, as well as nurturing other hidden human potentials. This article discusses the concept of edutainment and several mechanism to implement it comprehensively in Islamic Education. Keywords: Learning, Edutainment, Islamic Education